A case study on information technology usage at Temerloh police station / Nurul Jannah Zainuddin, Rohani Razak and Siti Nazirah Mohd Salleh - Zainuddin, Nurul Jannah; Razak, Rohani; Mohd Salleh, Siti Nazirah (2009)
Information Technology (IT) plays a major role for individual. According to Gupta and Ansari (2007), Information Technology (IT) refers to both the hardware and software that are used to store, retrieve and manipulate information. IT is only one of the tools to increase the efficiency, productivity and competitiveness in the business; various initiatives were taken to promote the use of technology among staff. This study tries to identify the level, impact and factors promoted Information Technology usage among staff at Temerloh Police Station. To gain data and information of staffs on IT usage at Temerloh Police Station, we use the questionnaires. A sample of 30 respondents from five departments: Administrative, Civil Military, Criminal Investigation, Commercial Criminal Investigation and Affair Department participated in the survey. This study found that staff at Temerloh Police Station often used IT in their daily work. The software and hardware were often used by the staff is Word Processing and printer. Using Information Technology also gives the biggest positive impact in increase job performance among staff and there are several factors that can promote the staff using Information Technology (IT). The highest factors that can promote staff to use Information Technology is strong support from top management. The organization should introduce an advance technology, establish meeting and provide appropriate and sufficient equipment to promote IT usage at Temerloh Police Station.